2020
DOI: 10.15766/mep_2374-8265.11005
|View full text |Cite
|
Sign up to set email alerts
|

A Mentor, Advisor, and Coach (MAC) Program to Enhance the Resident and Mentor Experience

Abstract: Introduction: While residents must meet standardized educational milestones to graduate, individualized mentorship and guidance can help them achieve personal and career goals. A novel mentor, advisor, and coach (MAC) program was created for residents of the Yale University Traditional Internal Medicine Residency Program to help them attain these goals. Methods: Internal medicine faculty were recruited into the MAC program and matched with residents, with each faculty paired with one to three mentees. A struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[1][2][3] Similar faculty-led initiatives exist within residency programs to support clinical development and attainment of resident career goals. 4 There is a dearth of literature, however, about resident-programs that provide specialty-specific advising to students. A "big sibling" program that paired students with surgery residents received positive reviews from residents and improved the students' experience.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…[1][2][3] Similar faculty-led initiatives exist within residency programs to support clinical development and attainment of resident career goals. 4 There is a dearth of literature, however, about resident-programs that provide specialty-specific advising to students. A "big sibling" program that paired students with surgery residents received positive reviews from residents and improved the students' experience.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Institutional programs such as the initiation or implementation of women in medicine groups are one of the measures taken to make progress. However, most interventions have been targeted for faculty with few intended to meet the needs unique to residents [ 12 , 13 ]. Here, we describe our experience with designing and sustaining an intervention that addresses the need for resident support as an effective approach that can be adopted by other institutions resolving to advocate for gender equity in medicine.…”
Section: The State Of Women In Medicinementioning
confidence: 99%
“…Designating a formal definition for each guidance method will lay the groundwork for individualizing the terms mentor, coach, and advisor. Table 1 recommends potential definitions that can be utilized across the medical community to distinguish individual faculty roles [ 7 ].…”
Section: Reviewmentioning
confidence: 99%
“…Extensive work has been published on the history, benefits, and application of each guidance strategy as well as program designs for implementing each approach. One recent study established that mentor, advisor, and coach (MAC) relationships during residency can enhance resident experiences and that the majority of participants benefited from the program [ 7 ]. Meanwhile, another analysis demonstrated that guidance in medical education can increase research opportunities, strengthen professional relationships, heighten professional development, and provide insight into career decisions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%